Phosphorus nutrition and its effect on the growth, yield attributes and seed yield of Mungbean (Plant Bulletin, 2025)
Phosphorus has a crucial role in the growth and development of mungbean to improve the quality as well as its grain yield. Therefore, to investigate the effect of varying phosphorus levels on growth and yield attributes under different mungbean varieties, a field experiment was conducted at Agronomic Research Farm, University of Agriculture Faisalabad. The experiment was carried out using a randomized complete block design with a split-plot arrangement and replicated thrice. Four phosphorus levels i.e. 0, 30, 60 and 90 kg ha-1 in main plots while three varieties viz. AZRI Mung-2018, PRI Mung-2018 and Chakwal Mung-2006 in subplots were maintained. The data related to phenology, growth, yield, and various yield-related traits were recorded following standard procedures. The results depicted that growth and yield parameters such as leaf area index, total dry matter, grain yield and biological yield were recorded highest for AZRI Mung-2018. This variety produced 14% more seed yield than Chakwal Mung-2006, and it was followed by PRI Mung-2018 which resulted in 6% more seed yield than Chakwal Mung-2006. Regarding different phosphorus levels, phosphorus supplementation at the rate of 30, 60, and 90 kg ha⁻¹ produced 16%, 37%, and 27% more seed yield as compared to control (0 kg ha⁻¹), respectively. The interaction effect of different cultivars and phosphorus levels was non-significant. Our study highlighted that maximum seed yield (1862 kg ha-1) was recorded under 60 kg ha-1 phosphorus application rate across different varieties, and this dose can be adopted to enhance the productivity of mungbean on sustainable basis.
Keywords: crop nutrition; Legume cultivars; Macronutrients; Phosphorus; Vigna radiata